The essential Buffett : timeless principles for the new economy - Hagstrom, Robert G., 1956- (Wiley, 2001)
Applying Buffett's principles to technology and international investing. From the bestselling author of The Warren Buffett Way and The Warren Buffett Portfolio comes The Essential Buffett: Timeless Principles for the New Economy. In this fresh take on Buffett's irrefutable investment methods, Robert Hagstrom shows readers how to apply Buffett's principles to technology and international investing using real-life case studies of successful fund managers like Legg Mason's Bill Miller.